Assessment of the labelling accuracy of spanish semipreserved anchovies products by FINS (forensically informative nucleotide sequencing). Issue 6 (June 2016) - Velasco, Amaya; Aldrey, Anxela; Pérez-Martín, Ricardo I.; Sotelo, Carmen G.
Abstract: Anchovies have been traditionally captured and processed for human consumption for millennia. In the case of Spain, ripened and salted anchovies are a delicacy, which, in some cases, can reach high commercial values. Although there have been a number of studies presenting DNA methodologies for the identification of anchovies, this is one of the first studies investigating the level of mislabelling in this kind of products in Europe. Sixty-three commercial semipreserved anchovy products were collected in different types of food markets in four Spanish cities to check labelling accuracy. Species determination in these commercial products was performed by sequencing two different cyt-b mitochondrial DNA fragments. Results revealed mislabelling levels higher than 15%, what authors consider relatively high considering the importance of the product. The most frequent substitute species was the Argentine anchovy, Engraulis anchoita, which can be interpreted as an economic fraud.